Bentuk Satuan Lingual dan Nilai Pendidikan Dalam Kearifan Lokal Pasatotang Suku Samawa - Rahmani, Nanda Hafizhah; Mahsun, Mahsun; Burhanuddin, Burhanuddin; Saharudin, Saharudin (Cetta: Jurnal Ilmu Pendidikan, 2025)
Language, culture, and education are interrelated in shaping the character of society. Language is the main tool for passing on culture and educational values, while culture shapes values ​​in education. Education plays a role in preserving language and culture through teaching history, literature, and local values. This study aims to describe the form of lingual units and educational values ​​in the local wisdom of the Pasatotang of the Samawa Tribe on Sumbawa Island, West Nusa Tenggara. Pasatotang, which means advice, is an oral tradition that contains moral messages, manners, and profound life values. This study combines structural linguistics and ethnolinguistic approaches to explore the language structure and cultural meaning contained in pasatotang, which plays a role in shaping the character and social behavior of society. The research data were obtained from the book Pasatotang by LATS Anorawi (2016), which consists of words, phrases, and sentences that function as lingual units in this tradition. Data collection methods include literature study techniques, reading techniques, and note-taking techniques to interpret lingual forms and educational values ​​in order to achieve the desired data with instruments in the form of table data analysis guidelines. Data analysis in this study was conducted by systematically reviewing documents through documentation techniques. The collected data were reduced, classified into themes and codes, then interpreted and presented in the form of narratives, tables, or images to illustrate the meaning behind the speech and support the research findings. This study found that the local wisdom of Pasatotang of the Samawa tribe contains lingual units in the form of words, clauses, and discourses, and contains religious, moral, and social educational values ​​that form noble and characterful characters that are associated with the theory of Ki Hadjar Dewantara.